1998
DOI: 10.3109/03639049809085631
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Solvent-Free Preparation Methods for Felodipine Surface Solid Dispersions

Abstract: Surface solid dispersions were prepared via physical mixture and were either heated in a vacuum dryer or in a microwave oven for different periods of time. The physical state of felodipine in solid dispersions was studied using differential scanning calorimetry and x-ray powder diffractometry. USP paddle method was used for felodipine dissolution studies. The use of vacuum or microwave energy led to a significant improvement of felodipine dissolution which was caused partly by the amorphous state of felodipine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…They showed that the solid dispersions had increased dissolution rates of nifedipine. Similar results were reported for the felodipine (Kerc et al 1998). Rodrigues et al prepared the microparticles of theophylline with hydrogenated palm oil (HPO) by the PGSS process demonstrating that the process enabled coprocessing of API with the excipient (Rodrigues et al 2004).…”
Section: Operations Where Scf Acts As Solute (Particles From Gassupporting
confidence: 88%
“…They showed that the solid dispersions had increased dissolution rates of nifedipine. Similar results were reported for the felodipine (Kerc et al 1998). Rodrigues et al prepared the microparticles of theophylline with hydrogenated palm oil (HPO) by the PGSS process demonstrating that the process enabled coprocessing of API with the excipient (Rodrigues et al 2004).…”
Section: Operations Where Scf Acts As Solute (Particles From Gassupporting
confidence: 88%
“…Microwave energy has been employed to change the crystalline state of a drug, instead of conventional heating. Kerč et al [8], using felodipine as a model drug and a porous silicon dioxide, reported that microwave energy can influence the crystalline status of the drug and the time of exposure plays an important role in achieving the amorphous state of the drug, improving consequently its dissolution rate. Microwave irradiation was also successfully used to obtain an inclusion complex of carvedilol and β-cyclodextrin as reported by Xianhong et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…The first attempt in this area was probably the dissolution rate enhancement of felodipine from solid dispersions by the heating of physical mixtures of the drug and carrier (amorphous silicon dioxide) either in a vacuum dryer or in a microwave oven. 13 Bergese et al, 14 with the long-term aim of increasing the bioavailability of several insoluble drugs, developed a microwave-induced diffusion method for generating activated drug/three-dimensional matrix nanocomposites. Microwaves have also been applied to induce changes in drug carriers that would retard drug release with alginate chitosan, bovine serum albumin, and pectin as matrices.…”
Section: Introductionmentioning
confidence: 99%